2020
DOI: 10.1186/s12894-020-00742-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of screening and treatment of Ureaplasma urealyticum infection on semen parameters in asymptomatic leukocytospermia: a case–control study

Abstract: Background Ureaplasma urealyticum (UU) infection, as well as asymptomatic leukocytospermia, whether it has effect on semen parameters and whether it needs screening and treatment is still a confusing and controversial topic for clinicians. Methods Among 1530 adult males who visited Guilin People's Hospital due to infertility, 295 were diagnosed with asymptomatic leukocytospermia, and 95 were further screened for UU-positive. 81 UU-positive asymptomatic leukocytospermia patients received 7-day or 14-day trea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…The results revealed that samples from subjects with leukocytospermia in the Leu and LA groups had lower sperm quality, indicating that the seminal leukocyte count was negatively correlated with sperm parameters not only in normal males but also in asthenozoospermic males. These results are consistent with those of previous studies 1 2 3 34 and reconfirmed the relationship between leukocytospermia and sperm parameters.…”
Section: Discussionsupporting
confidence: 93%
“…The results revealed that samples from subjects with leukocytospermia in the Leu and LA groups had lower sperm quality, indicating that the seminal leukocyte count was negatively correlated with sperm parameters not only in normal males but also in asthenozoospermic males. These results are consistent with those of previous studies 1 2 3 34 and reconfirmed the relationship between leukocytospermia and sperm parameters.…”
Section: Discussionsupporting
confidence: 93%
“…It was previously reported that the negative impact of bacteria potentially responsible for urogenital tract infections on routine sperm quality markers is often associated with supraphysiological levels of seminal leukocytes [40][41][42][43][44][45]. A positive correlation between the bacterial load and the occurrence of leukocytes recorded in our study agrees with previous observations in animals [44,45] as well as humans [41][42][43].…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies reported that compared with patients with nonleukocytospermia (non-LCS), decreased semen parameters (e.g., sperm concentration, progressive motility, normal morphology) were observed in asymptomatic leukocytospermia (LCS), while those with STI (e.g., UU)-positive leukocytospermia performed more significantly [ 5 , 15 ]. In this study, we aimed to investigate the prevalence of sexually transmitted pathogens by molecular methods in semen samples from infertile men with and without leukocytes and their effects on semen quality.…”
Section: Introductionmentioning
confidence: 99%